Effects of submerged fermentation on coffee quality in Coatepec, Veracruz, Mexico - Arrechea-Villacampa, Antonio (2026)
Introduction. Fermentation is a critical stage in the wet processing of coffee, with the potential to significantly modify its sensory profile. However, its influence on physical and sensory quality varies depending on the method applied. Objective. To evaluate the influence of two fermentation methods (aerobic and anaerobic) on the physical and sensory quality of a Coffea arabica L. blend (varieties Caturra, Mundo Nuevo, Costa Rica, and Geisha) cultivated in the Coatepec region, Veracruz, Mexico, and processed using the wet method. Materials and methods. The study was conducted during the 2025 harvest season (JanuaryÐMarch) at Finca Bímori, located in the coffee-growing region of Coatepec, Veracruz, Mexico. A completely randomized design (CRD) was used. Two fermentation methods were applied, with three replicates and mean comparisons (p < 0.05). During fermentation, the following variables were recorded: soluble solids (¡Brix), total dissolved solids (TDS), pH, temperature, electrical conductivity (EC), chemical oxygen demand (COD), and total organic carbon (TOC). Afterwards, moisture content, density, and final yield were evaluated in both dry parchment coffee and green coffee. Sensory quality was assessed according to the Specialty Coffee Association protocol. Results. A significant increase was observed in TDS, EC, COD, TOC, and ¡Brix, along with a decrease in pH under both methods. No significant differences were found in physical variables. The aerobic fermentation scored 80.8, with chocolate and caramel notes, while the anaerobic fermentation scored 82.7, with fruity and citrus notes. Conclusions. The aerobic and anaerobic fermentation methods applied to the coffee blend cultivated in the Coatepec region and processed through the wet method did not significantly influence the physical quality of the beans; however, the anaerobic method produced a more complex sensory flavor profile with greater aromatic diversity.